It takes a dimer to tango: Oligomeric small heat shock proteins dissociate to capture substrate - Santhanagopalan, I; Degiacomi, M; Shepherd, D; Hochberg, G; Benesch, J; Vierling, E (American Society for Biochemistry and Molecular Biology, 2018)
Small heat-shock proteins (sHsps) are ubiquitous molecular chaperones, and sHsp mutations or altered expression are linked to multiple human disease states. sHsp monomers assemble into large oligomers with dimeric substructure, and the dynamics of sHsp oligomers has led to major questions about the form that captures substrate, a critical aspect of their mechanism of action. We show here that sub-structural dimers of two plant dodecameric sHsps, Ta16.9 and homologous Ps18.1, are functional units in the initial encounter with unfolding substrate. We introduced inter-polypeptide disulfide bonds at the two dodecameric interfaces, dimeric and nondimeric, to restrict how their assemblies can dissociate. When disulfide bonded at the non-dimeric interface, mutants of Ta16.9 and Ps18.1 (TaCT-ACD and PsCT-ACD) were inactive, but when reduced, had wildtype-like chaperone activity, demonstrating that dissociation at non-dimeric interfaces is essential for sHsp activity. Moreover, the size of the TaCT-ACD and PsCT-ACD covalent unit defined a new tetrahedral geometry for these sHsps, different from that observed in the Ta16.9 X-ray structure. Importantly, oxidized Tadimer (disulfide bonded at the dimeric interface) exhibited greatly enhanced ability to protect substrate, indicating that strengthening the dimeric interface increases chaperone efficiency. Temperature-induced size and secondary structure changes revealed that folded sHsp dimers interact with substrate and that dimer stability affects chaperone efficiency. These results yield a model in which sHsp dimers capture substrate before assembly into larger, heterogeneous sHsp-substrate complexes for substrate refolding or degradation and suggest that tuning the strength of the dimer interface can be used to engineer sHsp chaperone efficiency.